Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1037/met0000462
|View full text |Cite
|
Sign up to set email alerts
|

Seeking a better balance between efficiency and interpretability: Comparing the likert response format with the Guttman response format.

Abstract: The Likert item response format for items is almost ubiquitous in the social sciences and has particular virtues regarding the relative simplicity of item-generation and the efficiency for coding responses. However, in this article, we critique this very common item format, focusing on its affordance for interpretation in terms of internal structure validity evidence. We suggest an alternative, the Guttman response format, which we see as providing a better approach for gathering and interpreting internal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Researcher Identity. The Researcher Identity Scale measures students' agency, community, interest, aspiration, and self-perceptions as someone who can contribute to investigations about a topic (Koo et al, 2021), and has been validated for use with high school students as a Likert-scale and Guttman scale (Wilson et al, 2022). In this study, researcher identity was derived by averaging the Guttman scale answers to twelve questions (Wilson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researcher Identity. The Researcher Identity Scale measures students' agency, community, interest, aspiration, and self-perceptions as someone who can contribute to investigations about a topic (Koo et al, 2021), and has been validated for use with high school students as a Likert-scale and Guttman scale (Wilson et al, 2022). In this study, researcher identity was derived by averaging the Guttman scale answers to twelve questions (Wilson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The Researcher Identity Scale measures students' agency, community, interest, aspiration, and self-perceptions as someone who can contribute to investigations about a topic (Koo et al, 2021), and has been validated for use with high school students as a Likert-scale and Guttman scale (Wilson et al, 2022). In this study, researcher identity was derived by averaging the Guttman scale answers to twelve questions (Wilson et al, 2022). When answering each question, respondents could choose from five text options, which translated to a numeric range from 1 to 5, where the first option (assigned the numerical value of 1 for analysis purposes) was the "lowest level" and the last option (assigned the numerical value of 5 for analysis purposes) was the "highest level".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there is widespread use of these procedures in survey research, literature within the field of measurement has cautioned the inherent assumptions tied to these analyses (Boone, 2016;Wilson et al, 2022). Harwell and Gatti (2001) classified such ordinal-to-interval conversion procedures as an appeal to Classical Test Theory (CTT), a measurement method with widely recognized limitations as compared to more robust psychometric methods like Item Response Theory (IRT; Wang, 1999).…”
Section: Advancing Assessment: Utilizing Item Response Theory and Ras...mentioning
confidence: 99%
“…
Wilson et al (2022) compared the Likert response format to an alternative format, which they called the Guttman response format. Using a Rasch modelling approach, they found that the Guttman response format had better properties relative to the Likert response format.
…”
mentioning
confidence: 99%